Nursing Students’ Perceptions On The Management Of Nursing Laboratory - Sari Ali Astuti; Wida Sulastri; Atlastieka Praptiwi (Journal of Nursing Care, 2019)
The nursing laboratory is a student place to practice their psychomotor skills related to nursing interventions. The changes in the nursing curriculum from the curriculum of 2000 to 2015 for the undergraduate level at Nursing Faculty of Padjadjaran University have an impact on the laboratory development in supporting the student to achieve their target study. It is essential to identify nursing students’ perceptions on the management of nursing laboratory from various aspects including physical aspects (infrastructure and material), learning processes, and human resources. This study used the descriptive quantitative approach to identify perceptions of nursing students about the nursing laboratory. The sample in this study was 402 students. A questionnaire used in the data collection. The data were analysed using percentage, median and IQR score were measured using the Likert scale. The results of the study found that the Physical and Safety aspects were the highest aspects with median value: 32 and the IQR value of 4. This study is expected to contribute to developing the nursing faculty laboratory as students’ need and as an evaluation for the laboratory staffs and lecturers in improving services for students in the laboratory.